Bringing down the duke ebook - Dunmore, Evie (League of Extraordinary Women, 2019)
“Dunmore is my new find in historical romance. Her A League of Extraordinary Women series is extraordinary.” —Julia Quinn, #1 New York Times bestselling author “This series balances friendship, politics, history, and romance in just the right mix.” —U.S. Representative Katie Porter A stunning debut for author Evie Dunmore and her Oxford suffragists in which a fiercely independent vicar's daughter takes on a powerful duke in a fiery love story that threatens to upend the British social order. England, 1879. Annabelle Archer, the brilliant but destitute daughter of a country vicar, has earned herself a place among the first cohort of female students at the renowned University of Oxford. In return for her scholarship, she must support the rising women's suffrage movement. Her charge: recruit men of influence to champion their cause. Her target: Sebastian Devereux, the cold and calculating Duke of Montgomery who steers Britain's politics at the Queen's command. Her challenge: not to give in to the powerful attraction she can't deny for the man who opposes everything she stands for. Sebastian is appalled to find a suffragist squad has infiltrated his ducal home, but the real threat is his impossible feelings for green-eyed beauty Annabelle. He is looking for a wife of equal standing to secure the legacy he has worked so hard to rebuild, not an outspoken commoner who could never be his duchess. But he wouldn't be the greatest strategist of the Kingdom if he couldn't claim this alluring bluestocking without the promise of a ring...or could he? Locked in a battle with rising passion and a will matching her own, Annabelle will learn just what it takes to topple a duke.... “With her sterling debut, Evie Dunmore dives into a fresh new space in historical romance that hits all the right notes.” — Entertainment Weekly “There is nothing quite so satisfying as seeing such a man brought to his knees by a beautiful woman with nothing to her name except an inviolable sense of her own self-worth.” — NPR